Investigation of factors affecting dissolution under biorelevant low velocity hydrodynamic conditions, using in vitro and in-silico methods - Liu, Bo (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2011)
The goals of the current study were to investigate the effect of hydrodynamics on the dissolution of non-disintegrating compacts in a low velocity environment. This work also studies the impact of hydrodynamics on the dissolution of immediate releasetabletsina flow-through apparatus, where a model was developed to simulate particulate dissolution. The dissolution of Benzoic Acid (BA) compacts was carried out in the flow-through apparatus at different inflow rates in order to determine the effectof low fluid velocity on the dissolution rate. The dissolution ratesof BA were not significant different under different inflow rates in the flow-through cell with a diameter of 22.6 mm. Hydrodynamics at different inflow rates was studied in the flow-through apparatus using a 3-D Computational Fluid Dynamics (CFD) model in order to interpret the effect of flow velocity, shear stress and shear rate on dissolution rate. The simulated result indicated that the flow reversal resultingfrom boundary separation may weaken the effect of the bulk flow rate on the dissolution rate of BA.
Keywords: Pharmaceutics, Ph.D.; Ph.D. Trinity College Dublin